PERBANDINGAN TINGKAT KEPUASAN PESERTA ASKES WAJIB DAN SUKARELA TERHADAP MUTU PELAYANAN KESEHATAN TINGKAT I = SATISFACTION OF COMPULSORY AND VOLUNTARY HEALTH INSURANCE PARTICIPANTS ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: PT. Askes has two types of membership, compulsory and voluntary. Factors which differentiate both of them are among others rate of premi, health service coverage at first level outpatient and location of primary health service. Compulsory participants are served community health center doctors, whereas voluntary participants by family physicians. Some positive aspects of family physicians do not guarantee better quality service than community health service. The study aimed to know the difference of satisfaction between Askes compulsory and voluntary patients with health service quality of community health center and family physicians. Methods: This was an analytic study which used a cross sectional design. There were 200 samples of Askes respondents who were chosen using proportional random sampling. Instruments used were closed questionnaires and in depth interview guide. Data were analyzed using t-test. Results: Average satisfaction of compulsory Askes patients with health service quality was higher than that of voluntary ones (112.58 versus 100.83